(untitled) (The Review of Diabetic Studies, 2025)
Background: Nursing and health education are integral components of public health systems. However, little is known about how nursing practices and health education initiatives correlate with public health outcomes in Saudi Arabia. The aim of the study: To evaluate nursing practices and health education efforts and determine their impact on selected public health indicators in Saudi Arabia. Methods: A cross-sectional survey was conducted among 500 nurses across five regions of Saudi Arabia. Participants completed a validated questionnaire on nursing practice quality, health education activities, and observed public health outcomes. Descriptive statistics, chi-square tests, and regression analyses were performed. Results: High levels of health education activities were significantly associated with improved community vaccination awareness (β = 0.42, p < 0.001) and preventive health behavior scores (β = 0.37, p < 0.001). Nurses with 5 or more years of experience reported better public health outcomes (p = .02). Conclusions: Effective nursing practices and structured health education programs have a positive influence on key public health outcomes. Strengthening training and policy support could enhance population health.